It's all about the dress : savvy secrets, priceless advice, and inspiring stories to help you find "the one" - Fenoli, Randy (Grand Central Life & Style ; Little, Brown [distributor], 2011)
The host of "Say yes to the dress" provides tips for choosing the perfect wedding dress, including styles, fabrics, fitting, the wedding party, and time line for planning.